The Legal Vacuum of Labor Protection for Freelancers in the Technology Sector - Sauqi, Azhari; Suparno, Suparno (Yayasan Adra Karima Hubbi, 2024)
Background. The rapid growth of the technology sector has created numerous new job opportunities, especially for freelancers. However, alongside the flexibility it offers, there exists a significant legal vacuum in labor protection for workers in this sector. Freelancers are often not recognized as “workers” under the law, resulting in a lack of protection such as social security, health insurance, pension benefits, and other employment rights. This regulatory gap creates vulnerabilities for workers concerning income uncertainty, exploitation, and work-related stress. This article discusses the legal vacuum and its impact on the physical, mental, and social well-being of freelancers in the technology sector, as well as proposing necessary steps to create more inclusive labor protection. More adaptive and comprehensive policy changes are required to address the challenges faced by freelancers in this digital economy era. Purpose. The growing gig economy, particularly in technology, has brought forward new forms of employment. However, these freelance roles often fall outside traditional labor laws, leading to gaps in protections and rights. Method. A qualitative analysis was conducted through interviews with freelancers and legal experts, along with a review of existing labor laws. Results. Freelancers face significant vulnerabilities, including lack of health insurance and pension benefits, leading to increased financial instability and work-related stress. Conclusion. A comprehensive overhaul of labor laws is necessary to protect freelancers, ensuring they have access to benefits such as health insurance, pension plans, and social security.